Challenges to Doctoral Education in Africa - Khodabocus, Fareeda (International Higher Education, 2016)
Doctoral education in Africa is at a turning point and African universities are called upon to act as the focal points for growth in African development. African Studies reveal that the growth of doctoral education in the leading universities in Africa are increasing but at a slow rate and universities, must be motivated to produce enough doctorates to contribute to growth of their knowledge economies. The need to create high-level skills demand on the job market is evinced and African universities must be driven by their governments, private sectors and academic communities to generate more doctorates in supply to its labor market.